Analisa Kekuatan Gantry Crane Tipe Ect-15 Pada Saat Di Gunakan Di Pelabuhan Kijing, Pontianak, Kalimantan Barat - Jalil Jalil (Departemen Teknik Kelautan Universitas Hasanuddin, 2021)
Lifting tools are aircraft or tools used to lift or move an item with a certain distance, size and weight. Gantry Crane is a type of tall upright portal crane that lifts objects with a hoist that is mounted on a hoist trolley and can move horizontally on rails or rail pairs attached to beams or work floors. The Kijing Terminal is a development of the Pontianak Port and is one of the National Strategic Projects (PSN). Gantry Crane Type ECT-15 indicates that the maximum and minimum carrying strength of the Gantry Crane ECT-15 Type must be adjusted to the size of the tool. The data obtained is very accurate, such as the height of the tool is a maximum of 12 m capable of lifting goods from a minimum of 1-14 tons where the lifting speed is 6/20 or 4.5 / 15, can cross 18 / 1.8 or 12 / 1.2, ending the transport of 20 / 1.5 or 30 /2.2 where the quantity to be transported or the dimensions transported N 83 R between 1000 or 1300, wheel diameter 500-630. The Gantry Crane ECT-15 T container has advantages such as strong lifting capacity, excellent design and simple structure. In addition to having the advantages of a Gantry Crane, it also has disadvantages including: Requires Clearance Area, Safety Supervision must be tighter, and more intensive maintenance (outdoor).